2023
DOI: 10.1093/ckj/sfad076
|View full text |Cite
|
Sign up to set email alerts
|

Early aging and premature vascular aging in chronic kidney disease

Abstract: Aging is the progressive decline of body functions and a number of chronic conditions can lead to premature aging characterized by frailty, a diseased vasculature, osteoporosis and muscle wasting. One of the major conditions associated with premature and accelerated aging is chronic kidney disease (CKD) which can also result in early vascular aging and the stiffening of the arteries. Premature vascular aging in CKD patients has been considered as a marker of prognosis of mortality and cardiovascular morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 184 publications
0
9
0
Order By: Relevance
“…However, treatment with 0.5% FF did not significantly affect pAMPK or PGC1α levels in the rat kidney. AMPK may also indirectly activate sirtuin 1 (SIRT1), a histone deacylase involved in many regulatory cellular processes and implicated in the control of cellular aging [ 23 ]. The level of SIRT1 was upregulated by 0.5% FF in the kidney of young but not old rats ( Figure 7 a), even though Sirt1 mRNA expression increased after treatment only in the old animals ( Figure 7 b).…”
Section: Resultsmentioning
confidence: 99%
“…However, treatment with 0.5% FF did not significantly affect pAMPK or PGC1α levels in the rat kidney. AMPK may also indirectly activate sirtuin 1 (SIRT1), a histone deacylase involved in many regulatory cellular processes and implicated in the control of cellular aging [ 23 ]. The level of SIRT1 was upregulated by 0.5% FF in the kidney of young but not old rats ( Figure 7 a), even though Sirt1 mRNA expression increased after treatment only in the old animals ( Figure 7 b).…”
Section: Resultsmentioning
confidence: 99%
“…Optimal kidney function is critical for healthy aging, and biomarkers of mortality are often associated with impaired kidney function [ 18 , 19 , 20 ]. Premature aging is associated with impaired kidney filtration and kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one possible explanation for the increased Ig levels in the plasma may be the increased levels of infiltrating B cells into organs. It is known that B cells infiltrate the kidney and other organs with age [ 19 ]. There are three main subsets of B cells: MZ, follicular (FO), and B-1 B cells.…”
Section: Discussionmentioning
confidence: 99%
“…5,61 NRF2 was shown to be an important regulator responsible for balancing prooxidative and antioxidative defence mechanisms as well as playing a central role in vascular aging and calcification and cellular senescence. 62 Therefore, nuclear-factor Kappa B signalling and resultant cytokine synthesis responsible inflammation has been suggested to be impaired. 5 On the other hand, moderate-intensity exercise improves neutrophil adherence, chemotaxis, phagocytosis, oxidative burst and degranulation, whereas high-intensity exercise depresses such functions, except leucocyte degranulation and chemotaxis, which remain unchanged.…”
Section: Immune Responsementioning
confidence: 99%
“…70,71 CKD has been associated with premature and accelerated aging as well as muscle wasting, frailty, vascular disease and systemic inflammation. 62 Initial studies have suggested that myostatin levels in the serum are elevated with increasing age, especially highest in physically frail elderly females, and are inversely correlated with the mass of skeletal muscle. 72,73 However, further studies have shown contradicting findings and have failed to report differences in myostatin levels based on age.…”
Section: Metabolismmentioning
confidence: 99%